Investigation of Standalone Solar Photovoltaic Water Pumping System With Reduced Switch Multilevel Inverter - Poompavai, T.; Kowsalya, M. (Frontiers in Energy Research, 2020)
Solar photovoltaic powered water pumping systems are becoming very successful in regions where there is no opportunity for connecting the grid. The photovoltaic technology converts solar energy into electrical energy for operating DC or AC motor-based water pump. In the case of a solar AC motor water pump, it engages two energy conversion stages (DC-DC and DC-AC) in the power conditioning unit. This usually resulted in increased size, cost, complexity and decreases efficiency of the entire system. In addition, the existing two-level inverter (DC-AC) stage generates higher harmonics in output voltage that deteriorates AC motor performance. As a consequence, a single energy conversion stage with more than two-level output voltage could be possible by utilizing multilevel inverters which replaces two-level inversion stage easily to get higher levels of output voltages as well for extracting best results from the motor. Moreover, they can able to operate with reduced switching frequency that certainly reduces switching losses. Still, the increased voltage levels comprise a higher number of power semiconductor switches, cumulative voltage stress and switching losses are making the system more complicated. In this paper an innovative seven-level inverter with five switches had been taken to investigate 0.5 H. P single phase induction motor water pump. This topology ensures minimum switching losses, lowering size along with less installation cost. In order to provide better insight into the working and performance of this proposed topology the simulation results performed in the MATLAB / Simulink environment and hardware implementation are depicted.